Organización contable en la empresa “Sal La Vaquita y Sal La Victoria” y su influencia en la gestión económica financiera del cantón Macará durante el periodo de noviembre y diciembre del 2015 - Vera Cedeño, Tatiana del Rocío (2017)
This work is fully justified, since it is fulfilling the requirement to obtain the degree in Accounting and Auditing, with the aim of strengthening the knowledge acquired in such prestigious Institution, in addition to the Owner of the Company Salt the Vaquita and Salt Victoria may have adequate control of its operations; the same ones that are reflected in the good service that is provided to its customers and the community in general, contributing in this way the economic development of the city and country. The objectives proposed in the present work were fulfilled in their entirety; the methodology used allowed for the inventory of values, goods, rights and obligations, as well as the control of the merchandise through the kardex by the weighted average system; the physical transactions in the daily book were recorded after physical verification; In addition, internal documents were made to control financial operations; Finally, the financial statements were prepared based on current accounting and tax regulations. Finally, a Accounting Accounting System was designed to allow the company "SAL LA VAQUITA AND SAL LA VICTORIA" to know the economic and financial situation and thus make the appropriate decisions